URGENSI CHECKS AND BALANCES KETATANEGARAAN INDONESIA DAN ISLAM - Bustamin, Bustamin; Jaya, Rony (JURIS (Jurnal Ilmiah Syariah), 2019)
The reform movement opened the door to implementation of the 1945 amendment to the constitution. The urgency of the Indonesian government's control system, which included the legislative, executive and judicial institutions, was quite a concern. This condition is based on the fact that during the Orde Baru the concept of the Trias Politica Montesquieu was castrated by the authorities. Unlike the case of the Islamic constitutional system, the concept of mutual control was much more familiar when Khulafaur Rasyidin Umar bin Khattab called six (six) high-ranking friends to find a replacement. This was later considered the first Syura Institute in Islamic history. The purpose of this paper is to recognize the urgency of checks and balances in the Indonesian government system and in the Islamic state administration. This article uses a library research method with a qualitative descriptive approach, which is then analyzed using the interactive analysis model of Miles, Huberman, and Saldana. The results show that following the amendment of the 1945 Constitution, the legislature, including the DPR and the DPD, has taken control of the executive and the Supreme Court and the Constitutional Court as a judicial body can control each other and establish a balance between these institutions. While the Islamic constitutional system in the Fiqh study of Siyasah was already familiar with the separation of powers and the separation of powers in the institutions of Tasyri'iyah, Tanfidziyah and Qada'iyah.